El concepto de parte en el proceso de exequátur. Nota a la STJCE de 23 de abril de 2009 - Durán Ayago, Antonia (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
This sentence deepens on the concept of part utilised in the article 43,1 of the Regulation (EC) 44/2001. Specifically, it is requested that the ECJ explains if should consider part, to effects of appealing a resolution of exequatur, to the creditor that exercises an action in name and payable by its debtor, although it has not formally acted as a procedural part in the litigation in which another creditor of that debtor formulated such application.